Bulk RNA sequencing of erythroblasts from a pair of SF3B1-mutated and SF3B1-wildtype induced pluripotent stem cell (iPSC) lines - Thier, Jonas; Hellström-Lindberg, Eva; Moura, Pedro; Lundin, Vanessa (Karolinska Institutet, 2025)
This dataset consists of bulk RNA sequencing data of MACS-separated GPA+ erythroblasts obtained from a pair of induced pluripotent stem cell (iPSC) lines with and without SF3B1-mutation, generated from an MDS patient (Asimomitis G et al. 2022, Blood Advances). The objective of this data collection was to assess how SF3B1 mutation changes the molecular profile of RNA splicing in erythropoiesis.

This dataset includes minimally processed, visualisation-ready .bam format sequencing data for both of the lines.

Processing:
MDS patient iPSC line-derived hematopoietic stem and progenitor cells (HSPC) were cultured for 14 days in erythroid specification media (StemPro-34 SFM [Gibco] + 1% Pen/Strep [Cytiva], 2 mM L-glutamine [Sigma-Aldrich], 3.5 µM 1-Thioglycerol [Sigma-Aldrich], 1% Bovine Albumin Fraction V [Gibco], 150 µg/mL holo-transferrin [Sigma-Aldrich], 2 U/mL erythropoietin [Pfizer], 50 ng/mL Stem Cell Factor [PeproTech] and 50 ng/mL interleukin-3 [PeproTech]).
At Day 14 of culture, mixed glycophorin A-positive (GPA+) erythroblast samples were isolated through MACS. Cells were lysed in RLT (Qiagen) + 40 mM dithiothreitol (Sigma-Aldrich) and RNA extraction was performed with RNeasy Micro Kit (Qiagen) with RNase-free DNase treatment according to the manufacturer’s protocol. RNA integrity numbers (RIN) were estimated using Agilent RNA 6000 Pico Kits (Agilent Technologies, CA, USA). A minimum RIN value of 6.5 was considered adequate. RNA sequencing (RNAseq) libraries were prepared from total RNA using SMARTer Stranded Total RNA-Seq Kits v2 - Pico Input Mammalian (Takara Bio, Japan), including enzymatic ribosomal depletion steps. Libraries were sequenced using an Illumina Novaseq 6000 S4 (Illumina, CA, USA) with paired-end 150bp configuration. Reads were pre-processed with TrimGalore v. 0.6.7 using CutAdapt v. 3.5 and BAM files were generated through via two-pass alignment with STAR v. 2.7.9a against the GRCh38.p13 human genome assembly.

The dataset consists of 13 files:
- 2 .bam files, one for the SF3B1-mutant sample and one for the wildtype sample;
- 2. bai bam index files, one for each sample to facilitate analysis of the .bam files.
- 8 .fastq raw data files, corresponding to a paired-end run of the two samples in two different lanes (2 x 2 x 2).
- 1 gene-collapsed read count matrix (.txt) summarising read counts for both samples.

The documentation file iPSCEB_FileList.txt contains a full list of the files in the dataset.
The total size of the dataset is approximately 80 GB.

Syftet med denna datainsamling var att bedöma hur SF3B1-mutation förändrar den molekylära profilen för RNA-splitsning vid erytropoes. Denna datauppsättning består av RNA sekvensering av erytroblaster från ett par av SF3B1-muterade och SF3B1-vildtyp inducerade pluripotenta stamcell (iPSC). Se den engelska beskrivningen för mer information.
RNA sekvensering av erytroblaster från inducerade pluripotenta stamcellslinjer (iPSC) med vildtyp och muterad SF3B1
Keywords: Myelodysplastic Syndromes; Myelodysplastiskt syndrom; Myelodysplastic-Myeloproliferative Diseases; Myelodysplastiska-myeloproliferativa syndrom; Induced Pluripotent Stem Cells; Inducerade pluripotenta stamceller; iPSC; iPSC; mds-rs; mds-rs; sf3b1; sf3b1; Cell Biology; Cellbiologi; Genetics and Genomics; Genetik och genomik; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi; Hematology; Hematologi; Cancer and Oncology; Cancer och onkologi